PTU-040 How Should Miss Rates for Cancer and Large Polyps Be Monitored at A Local Level? Retrospective Analysis of Repeat Colonoscopies at a District General Hospital. (17th August 2016) - Meade, S; Mcnair, A
Abstract : Introduction: Caecal intubation and adenoma detection rates are key performance indicators (KPI) used to assess the quality of colonoscopy. Post-colonoscopy colorectal cancer (PCCRC) rates have recently been suggested as an additional KPI. Most studies estimate PCCRC rates by identifying the proportion of patients with diagnosed colorectal cancer (CRC) who have had a colonoscopy within 3 years of their diagnosis. This is labour intensive requiring evaluation of ≥2 databases. We describe a simplified method for estimating PCCRC rates. Aim: To estimate the PCCRC rate using data from the endoscopy database alone. To identify all patients who had ≥2 colonoscopies over a 3 year period and those with CRC at the latest colonoscopy. To estimate the miss rate for larger (>20 mm) polyps. Methods: We identified all patients on our endoscopy database (Adam, Fujifilm) who had a colonoscopy from 2010–12 and had a repeat colonoscopy within the next 3 years. We merged initial colonoscopy data with data of those patients found to have CRC and used conditional formatting to flag up duplicate procedures. Patients found to have CRCs or polyps >20 mm in the repeat procedure, not noted at their initial endoscopy, were identified. This data was used to calculate a 'miss rate' for these lesions. Results: Between 2010 and 2012, 4961 colonoscopies were performed. In total 192 cancers were identified during this period. 237, 150, 225 and 128 repeat colonoscopies were performed within the same year and at 1, 2 and 3 years respectively. Of the 150 repeat procedures performed the following calendar year, indications included polyp surveillance (78), post-operative cancer surveillance (20), HNPCC or FAP (15), family history of CRC (8), anaemia (7), altered bowel habit (6) and other (16). In this group, 42 had polyps >20 mm and 6 had cancers. 3 of the cancers were in the ascending colon and the remaining three were missed at sites reported to have been examined in the previous study. This resulted in a missed polyp rate of 38.6%, a 'missed cancer rate' at one year of 6/150 patients (4%) and an overall 'missed cancer rate' of 0.12% or 1 in 827 colonoscopies. 2 cancers were found in patients who had a repeat colonoscopy after 2 years, both in the ascending colon. There were no missed cancers on repeat colonoscopy within the same calendar year or at three years. Conclusion: Data readily obtainable from the endoscopy reporting system can be used to determine the rate of missed cancers. Our results are similar to that reported in other studies employing more complex and time-consuming methodology. This alternative approach can be used by units to confirm their local PCCRC rate, large polyp miss rates and potentially identify endoscopists whose miss rates are unacceptably high. Disclosure of Interest: None Declared